Hispanic Threat and Police Strength in U.S. Municipalities: The Moderating Influences of Nativity and Region. (6th September 2021) - Holmes, Malcolm D; Painter, Matthew A
Abstract: A key question of research on crime control is whether the level of police strength in cities primarily represents citizens' collective interest in cutting crime, or whites' interest in exerting control over minority populations in a racially divided society. Minority threat theories maintain that whites and police authorities seek to protect their interests by mobilizing their political power to enhance police strength in cities with relatively large minority populations. Research testing this hypothesis examines the relationships of percent black and percent Hispanic to the strength of police departments. Studies of blacks support minority threat theories, but the limited research on Hispanics does not. We extend research on Hispanics by incorporating nativity and region into an analysis of cities of 100, 000 or more population in 2010. Noteworthy findings include complex interactions involving those predictors. Percent native-born Hispanic has a stronger negative relationship with police strength at higher levels of Hispanic-white residential segregation, but only in southwestern cities. Percent black is associated with increased police strength at higher levels of black-white segregation, but only in non-southwestern cities. These findings indicate that nativity, segregation, and regional context may jointly shape the mobilization of coercive crime control, sometimes in unexpected ways.